Nitrite Oxidation Kinetics for a Better Understanding of the Processes in the CAFOs Effluents Treatment - Fleite, Santiago Nicolás (2021)
Nitrite is an essential substance in the nitrification process; its oxidation in nature is carried out by the so-called nitrite oxidation bacteria (NOB). Understanding nitrite dynamics in natural waters or manure-contaminated waters (wastewaters) is fundamental to adjust treatment systems used in concentrated animal feeding operations (CAFOs). The aim of this work was to study the nitrite oxidation dynamics considering the effects of the DO concentrations and temperature variations and define a model capable of describing this process. For these purposes, the nitrite oxidation kinetics is characterized, analyzing the effect of relevant factors (microbial growth, pH, temperature and DO) under forced aeration (A) and anoxic conditions (NA) at 5, 10 and 20ºC. Results showed marked effects of the temperature and OD in NOB growth rate and therefore, nitrite oxidation rate. At 20ºC, there were significantly higher rates of nitrite oxidation under NA condition than in A condition whereas at 5ºC this relation was the opposite. This suggests that at 20°C OD deficiency does not inhibit the growth of NOB, while at low temperatures (≤ 10°C), the OD is a conditioning factor for NOB growth. In addition, these results show that competition with other microorganisms strongly depends on temperature and oxygen concentration.